Caracterização genética do pirarucu Arapaima gigas (Cuvier) (Teleostei, Osteoglossidae) da bacia Tocantins-Araguaia, estado do Mato Grosso - Marques, Débora Karla Silvestre (2003)
In South America the osteoglossiforms are represented by the Arapaima and the Osteoglossum sorts, which are mostly found in the Amazonic basin, Tocantins Araguaia. There are virtually no genetic studies on this group, which highlights conservation groups need for information. The Arapaima gigas species, of the hydrographic basin Tocantins Araguaia, showed a 2n=56 chromosomes, with cariotypical formula: 28M/SM+28ST/A. Silver nitrate marking revealed a simple RON, located intersticially in the shorter arm of pair three, confirmed by a fluorescent hybration in situ, with a rDNA 18S probe, that highlighted a polymorphism in the RON sites. The constituent heterocromatin was found in the centromerical region of all chromosomes. The molecular genetic studies with RAPD marker showed the presence of only one Arapaima gigas population, with a significant intrapopulational variation. The results obtained in this work are an important contribution to the understanding of the genetics of the Arapaima gigas species and the Osteoglossiforms group, providing, moreover, subsidies for genetic handling and conservation of the Arapaima gigas species in the Médio Araguaia, state of Mato Grosso do Sul, Brazil.